A fluid mechanics explanation of the effectiveness of common materials for respiratory masks. (October 2020) - Maher, Blake; Chavez, Reynaldo; Tomaz, Gabriel C.Q.; Nguyen, Thien; Hassan, Yassin
Highlights: Filtration efficiency of common materials for respiratory masks are investigated. Effects of materials to the upstream-downstream fluid flow regions are measured. One-layer masks have similar efficiency; multilayer masks' efficiency is greater than 90%. Comfortable-effective masks can be made from multilayer cotton and non-woven fabric. Washing masks reduces effectiveness; masks should be used a limited number of times. Abstract: Objectives: Face masks are an important component of personal protection equipment employed in preventing the spread of diseases such as COVID-19. As the supply of mass-produced masks has decreased, the use of homemade masks has become more prevalent. It is important to quantify the effectiveness of different types of materials to provide useful information, which should be considered for homemade masks. Methods: Filtration effects of different types of common materials were studied by measuring the aerosol droplet concentrations in the upstream and downstream regions. Flow-field characteristics of surrounding regions of tested materials were investigated using a laser-diagnostics technique, i.e., particle image velocimetry. The pressure difference across the tested materials was measured. Results: Measured aerosol concentrations indicated a breakup of large-size particles into smaller particles. Tested materials had higher filtration efficiency for large particles. Single-layer materials were less efficient, but they had a low pressure-drop. Multilayer materials could produce greater filtering efficiency with an increased pressure drop, which is an indicator of comfort level and breathability. The obtained flow-fields indicated a flow disruption downstream of the tested materials as the velocity magnitude noticeably decreased. Conclusions: The obtained results provide an insight into flow-field characteristics and filtration efficiency of different types of household materials commonly used for homemade masks. This study allows comparison with mass-produced masks under consistent test conditions while employing several well-established techniques.